What Is the Effect of Strength Training on Pain and Sleep in Patients with Fibromyalgia? - Bevilacqua G.G.* (2017)
Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved.Objective: The study aimed to investigate the effect of an 8-wk structured strength training program on pain and sleep quality in patients with fibromyalgia. Design: Fifty-two patients with fibromyalgia were evaluated; 31 submitted to strength training and 21 comprised the control group. The instruments used were the Fibromyalgia Impact Questionnaire and The Pittsburgh Sleep Quality Index. The questionnaires were applied before the first training session, at 12 sessions, and after 24 sessions. Descriptive statistics (mean, SD, and frequency) and inferential tests were used. Results: After 8 wks of intervention, significant differences were found between groups in subjective quality of sleep (P = 0.03), sleep disturbance (P = 0.02), daytime dysfunction (P = 0.04), and total sleep score (P < 0.01). The correlation analysis using Spearman's test indicated a positive relationship between the variables of pain intensity and sleep quality (P < 0.01); when pain intensity increased in patients with fibromyalgia, sleep quality worsened. Conclusions: Strength training is safe and effective in treating people with fibromyalgia, and a significant decrease in sleep disturbances occurs after 8 wks of intervention.